FACTOR INFLUENCING COMPLIANCE OF MASK USAGE AMONG BANGKALAN SUB-DISTRICT COMMUNITY DURING COVID-19 PANDEMIC - Hatimul Asmy; Nanik Setijowati; Khuznita Dasa Novita (Journal of Community Health and Preventive Medicine, 2022)
Bangakalan Sub-district occupies with the most patients infected by COVID-19 in Bangkalan Regency. Meanwhile, Bangkalan Regency itself has a significant number of COVID-19 patients. Various efforts are continuously have been done to control the rate of COVID-19 transmission, and one of the efforts is mask usage. Mask usage compliance can be influenced by several factors. This study aimed to find out which factors can significantly influence mask usage among the Bangkalan Sub-district community. This study used an analytical observation with a cross-sectional approach and obtained 100 samples. The number of respondent who compliant were 32 people (32%) (male 8 (8%), female 24 (24%), moderately compliant 33 people (9% male (9%), female 24 (24%)) and 35 people less compliance (male 13 (13%), female 22 (22%)). Based on the crosstab analysis Chi square test, only enabling and reinforcing factor that correlated with mask usage compliance. In enabling factor, there are two elements that are significantly related to mask usage compliance : providing spare masks whenever leaving the house (p-value=0,027) and good mask maintenance (p-value=0,000). In reinforcing factor, there are two elements that are significantly related to mask usage compliance : receiving warnings on mask usage from co-workers/schoolmates/college friends (p-value=0,002) and receiving warnings on mask usage from community leaders (p-value=0,040). The ordinal regression analysis showed  factors that did not significantly  influence mask usage compliance were predisposing factor (p-value = 0,452) and enabling factor (p-value = 0,527). Meanwhile, reinforcing factor (p-value = 0,001) significantly influenced mask usage compliance. When these three factors were described, the results of the ordinal regression showed ease of getting mask (p-value = 0,000), good mask maintenance (p-value = 0,037), receive warnings through social media (p-value = 0,043), and recieving warnings from the community leaders (p-value = 0,046) significantly influenced mask usage compliance among Bangkalan Sub-district community during COVID-19 pandemic.